Culturable organotrofic bacteria from high-altitude andean lakes - Gorriti, Marta Fabiana (2011)
The Andean Altiplano is a sedimentary volcanic plateau at about 4.000 m. Several lakes in the Altiplano are formed over evaporitic endorheic basins. These aquatic ecosystems present extreme conditions (high solar irradiance, arid conditions, low nutrient concentrations, heavy metals, large temperature fluctuations) and are a source of microorganisms with potential biotechnological applications. Lately, many studies have reported that the assessment of bacterial diversity by cultivation-independent methods is the most appropriate for studying diversity, owing to the existence of a host of unculturable. However, cultivation remains the preferred method for the acquisition of an accurate picture of the physiology and complex ecological interactions in which microorganisms engage. In this study, we attempted to determine the culturable bacterial diversity and extend the culture collections of Andean lakes in Argentina. Bacteria were isolated from Socompa and Diamante lakes in the Argentinean Puna. They were grown in different broth: LB, MGM, PY and 6WS. The pure and cellular morphology were determined by phase contrast microscopy and Gram stain. Bacterial diversity among the isolated was evaluated by PCR-amplified 16S rDNAs followed by phylogenetic analysis of 16S rDNA sequences. Twenty six strains were found. A neighbor-joining tree of the partial 16S rDNA sequences resulted in the division of the 18 strains of Socompa into two major groups, 14 strains of γ-Proteobacteria (77.7%) and 4 strains of Firmicutes (22.3%). Eigth strains of Diamante resulted in the division into 6 strains of Firmicutes (75%) and 2 strains Actinobacteria (25%). The γ-proteobacteria was group more diversity, including several genus: Salinivibrio, Shewanella, Pseudomona, Halomona, Aeromona, Idiomarina and Chromohalobacter. Additionally, seven new species candidates were found in Socompa, based on similarities of the 16S rDNA sequences to those of previously reported species.